Mailbox 27 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
MailboxMany of you told us in the User Survey how much you appreciate the exchange of experiences in Spore and how it should be expanded. Well, Mailbox is the perfect place. The floor is yours!